Analysis Of Demand For Health Insurance Business During The Indonesian Covid Pandemic - Neni Rosnani; Rini Hastuti; Erlina Puspitaloka Mahadewi (International Journal of Health and Pharmaceutical (IJHP), 2022)
The implementation of BPJS in Indonesia nine years ago, seems to have had an impact on a number of insurance companies also demand of the health insurance during pandemic in Indonesia. This mandatory program from the government inevitably affects the competitive landscape of the insurance industry in Indonesia, especially private insurance companies that serve health and other private insurance companies. Healthcare insurance competition is expected to become a mechanism capable of creating efficiency that functions as a tool to protect consumers and business actors. The Indonesia government policy is one of the state-owned insurance companies, PT. Askes (Persero) changed its name to BPJS which applies to all people. Currently PT. Askes (Persero) changed to BPJS which serves all Indonesian citizens without any difference. This study uses a qualitative method, aiming to analyze the development of demand trend in health insurance in Indonesia, its developments and implications, especially in the world of healthcare insurance business in Indonesia. From demand of health insurance business and competition, it is hoped that efficient, effective, and high-quality production will be achieved. The goal of this research is to highlight what are the things that benefit consumers because they are given the opportunity to have a choice of quality products and can buy at competitive prices which tend to be relatively cheap. This study also aims to analyze the demand for health insurance included: utilization of inpatient, utilization of health insurance and comparison literature review of inpatient and outpatient costs based on the type of social health insurance in Indonesia, public and private health facilities.